Find the product
(i) 2x(3x + 5xy) (ii) a2(2ab - 5c)
(i) 2x(3x + 5xy) = 2x x 3x + 2x x 5xy
= (2 x 3) X x X x + (2 x 5) X x X xy
= 6x2 + 10x2y
(ii) a2(2ab - 5c) = a2 x 2ab + a2 x (-5c)
= (a x 2) x a2 x ab + [1 x (- 5)] x a2 x c
= 2 x a2b + (- 5) x a2c
= 2a3b - 5a2c
Carry out the multiplication of the expressions in each of the following pairs
4p, q + r
Carry out the multiplication of the expressions in each of the following pairs
ab, a - b
Carry out the multiplication of the expressions in each of the following pairs
a + b, 7a2b2
Carry out the multiplication of the expressions in each of the following pairs
a2 - 9, 4a
Carry out the multiplication of the expressions in each of the following pairs
pq + qr + rp, 0
Complete table.
First expression | Second expression | Product | |
(i) (ii) (iii) (iv) (v) |
a x + y - 5 p 4p2q2 a + b + c |
a + c + d 5xy 6p2 - 7p + 5 p2 - q2 abc |
.... .... .... .... .... |